Gov-aargh-nance: "Even Criminals Need Law and Order" - Olaf J. de Groot; Matthew D. Rablen; Anja Shortland (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
We present a theoretical model postulating that the relationship between crime and governance is "hump-shaped" rather than linearly decreasing. State failure, anarchy and a lack of infrastructure are not conducive for the establishment of any business. This includes illegal businesses, as criminals need protection and markets to convert loot into consumables. At the bottom end of the spectrum, therefore, both legal business and criminal gangs benefit from improved governance, especially when this is delivered informally. With significant improvements in formal governance criminal activities decline. We use data from the International Maritime Bureau to create a new dataset on piracy and find strong and consistent support for this non-linear relationship. The occurrence, persistence and intensity of small-scale maritime crime are well approximated by a quadratic relationship with governance quality. Organised crime benefits from corrupt yet effective bureaucrats, and informally governed areas within countries.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: K42; P48; 330; Governance; Crime; Piracy; Informal Institutions; Law enforcement